THE FACTORS AFFECTING TAX AVOIDANCE - Febriani Cristina Susianti Magdalena; Meiliana Rosa Indah (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2024)
This study examine the effects of capital intensity, net profit margin, leverage, corporation risk and firm size on tax avoidance. This study uses a sample of consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. This study using a purposive sampling method with a sampling of 75 firms. This study use panel data regression analysis. The results are capital intensity, net profit margin, leverage, and corporation risk have no significant effect on tax avoidance. Meanwhile, firm size has a significant effect on tax avoidance.